Complications of Cesarean Delivery Based on Robson's Classification in Women Referred to Hospitals Affiliated to Shiraz University of Medical Sciences: A Cross-Sectional Study - Zoheh Rokesh; Mahnaz Zarshenaz; Naemeh Tayebi; Marzieh Akbarzadeh (Mashhad University of Medical Sciences, 2023)
Background & aim: WHO proposed using the Robson Ten Group Classification System (TGCS) for assessing, monitoring, and comparing cesarean section (CS) rates. This study aimed to identify which group of women have more complications after CS based on TGCS in Shiraz maternity teaching hospitals.Methods: This cross-sectional study included a sample of 1787 pregnant women who underwent cesarean section. From September to November 2018, convenience sampling was carried out at selected maternity teaching hospitals affiliated with Shiraz University of Medical Sciences, Shiraz, Iran. Demographic, obstetric, and fertility-related data were collected through personal interviews and a review of CS records. This study employed the TGCS to classify the women based on their obstetric data. Descriptive statistical analysis was done using SPSS software (version 23).Results:  Out of the 1787 patients, 455 (25.5%) had planned and 1332 (74.5%) had emergency CS. Complications of CSs included three causes: surgical, maternal, and neonatal. Surgical complications were the most prevalent in groups 5, 10, and 8; maternal complications were the most prevalent in groups 5, 2, and 10; and neonatal complications were the most prevalent in groups 5, 2, and 10. The most common CS complications were breastfeeding disorders (56.1%) and bladder adhesions to the uterus (27.5%). In total, 563 (25%) patients had surgical complications, 1077 (49.6%) had maternal complications, and 531 (24.4%) had neonatal complications.Conclusion: Most complications occurred in cases where the women had a previous history of CS (group 5). It seems essential to develop more efficient strategies to prevent unnecessary CSs.